UK Guidelines for Lipomodelling of the Breast on behalf of Plastic, Reconstructive and Aesthetic Surgery and Association of Breast Surgery Expert Advisory Group. Issue 2 (February 2022) - Skillman, Joanna; McManus, Penelope; Bhaskar, Pud; Hamilton, Stephen; Roy, P.G.; O'Donoghue, J.M.
Summary: Lipomodelling has become increasingly popular for reconstructive, aesthetic and therapeutic indications. The guidelines summarise available evidence for indications, training, technique, audit and outcomes in lipomodelling and also highlight areas for further research.